2012
DOI: 10.1371/journal.pntd.0001538
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Trachoma in South Sudan: Assessing the Health Losses from a Condition of Graded Severity

Abstract: IntroductionTrachoma is a disease that can lead to visual impairment and ultimately blindness. Previous estimates of health losses from trachoma using the Global Burden of Disease methodology have not, however, included the stage prior to visual impairment. We estimated the burden of all stages of trachoma in South Sudan and assessed the uncertainty associated with the severity and duration of stages of trachoma prior to full blindness.MethodsThe prevalence of trachoma with normal vision, low vision and blindn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The observation that TT was more prevalent in women than men is a finding that is well accepted, possibly this is due to the number of increased recurrent trachoma infections in women resulting from frequent contacts with children [31]. It is important to note that not all cases of trachomatous trichiasis lead to cornea opacities and impaired visual acuity [43] and that some of the cornea opacities seen in the community are not caused by trachoma but may be caused by other cornea infections and concurrent use of traditional medicines for treatment. Moreover the observed cases may be old prevalent cases and may need to be verified.…”
Section: Discussionmentioning
confidence: 93%
“…The observation that TT was more prevalent in women than men is a finding that is well accepted, possibly this is due to the number of increased recurrent trachoma infections in women resulting from frequent contacts with children [31]. It is important to note that not all cases of trachomatous trichiasis lead to cornea opacities and impaired visual acuity [43] and that some of the cornea opacities seen in the community are not caused by trachoma but may be caused by other cornea infections and concurrent use of traditional medicines for treatment. Moreover the observed cases may be old prevalent cases and may need to be verified.…”
Section: Discussionmentioning
confidence: 93%
“…However, in Tanzania, severe infection, repeated infections, and both severe and repeated infection in children under the age of 10 years led to trichiasis within 5 years [12]. While people with untreated trichiasis will ultimately become blind, a study in South Sudan has found that between 5 and 12% of people with trachoma have normal vision with trichiasis [13]. …”
Section: Clinical Picturementioning
confidence: 99%
“…Given the high prevalence of trachoma in South Sudan 12 , 31 in particular, it is surprising that the prevalence of TF among the refugee population was so low. This low prevalence has been noted in other settlements serving refugees from South Sudan, for example in Sudan and in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%